Para além da tela: o efeito de diferentes interfaces gráficas de jogos educacionais no desempenho de estudantes com e sem autismo em atividades matemáticas - Souza, Andiara Cristina de (Universidade Federal de São Carlos, 2024)
The difficulties faced by Brazilian students in teaching mathematics and the growing number of people with ASD included in mainstream schools have led to the adoption of digital educational games (DEGs) as teaching resources to facilitate the learning of this subject. However, despite the increasing use of these resources, little is known about the relationship between the design of the graphical user interface and the performance of students, especially students with ASD. Discussing the design of the graphical user interface (GUI) of DGEs and its accessibility is a highly relevant topic. This is because it can provide a reinforcing or non-reinforcing experience for the user, generating facilities or barriers to the use of digital resources. Accessibility guidelines have been developed to make GUI more accessible and user-friendly. However, there are still gaps in the literature, especially with regard to research aimed at analyzing the relationship between GUI in DEGs and the mathematical learning of students with autism. The aim of this study was to evaluate the impact of the GUI of mathematical DEGs on the attentional process, engagement, and performance of students with autism through the analysis of eye behavior. Chapter 1 aimed to discuss the use of DEGs in math teaching. To this end, a bibliographical survey was carried out of studies that have already been carried out that present the objectives and perspectives of DEGs as a tool for teaching mathematics. Chapter 2 aimed to map empirical research in the literature that evaluated guidelines for digital accessibility involving people with Autism Spectrum Disorder (ASD), by means of an integrative literature review. Based on the bibliographic surveys carried out in the first two chapters, an eye-tracking study was conducted in Chapter 3, which aimed to compare the eye behavior of children with and without autism when performing simple addition tasks (adding up to 10) DEGs made available on the web. The results indicated that children participating in the study with and without autism of similar age and mathematical input repertoire, when exposed to the same teaching conditions, do not show significant differences in performance in GDEs. In chapter 4, still using the data obtained through eye-tracking, it was verified how the design of the graphic interface of GDEs aimed at teaching mathematics can become a predictor of failure and exclusion of children with ASD. The results showed that complex platforms can negatively interfere with the performance of students with ASD in their interaction with mathematical concepts, hence the importance of a critical evaluation of these by parents, teachers, and therapists. Also, poorly accessible interfaces can perpetuate the view of disability of people with ASD brought about by the overvaluation of the diagnosis, which generates micro-exclusions. In general, the studies revealed that promoting educational practices based on GDEs for teaching mathematics requires parents, teachers and therapists to have the knowledge to critically analyze them. This is because the type of graphic interface can be a predictor of success or failure for students with ASD in learning mathematics and can contribute to inclusive or excluding mathematics. Future studies are suggested in order to broaden the discussion on the relationship and impacts of the GUI of GDEs and the mathematical learning of students with ASD.
Beyond the screen: the effect of different graphical interfaces of educational games on the performance of students with and without autism in mathematical activities
Keywords: Transtorno do espectro do autismo; Aprendizagem matemática; Interface gráfica; Jogos educacionais digitais; Rastreamento ocular; Autism spectrum disorder; Mathematical learning; Graphical interface; Digital educational games; Eye tracking; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::PROCESSOS PERCEPTUAIS E COGNITIVOS; DESENVOLVIMENTO